2007
DOI: 10.1038/sj.pcan.4501019
|View full text |Cite
|
Sign up to set email alerts
|

Bone health in prostate cancer patients receiving androgen-deprivation therapy: the role of bisphosphonates

Abstract: Androgen-deprivation therapy, a mainstay in the treatment of locally advanced and metastatic prostate cancer, is associated with significant bone loss and related complications, such as fracture. Bisphosphonates, osteoclast inhibitors, are effective in preventing skeletal-related events in patients with metastatic prostate cancer and also in preventing bone loss in patients with locally advanced disease. Understanding the management of bone health, including identifying patients at risk, the most appropriate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Some non-systematic reviews and specialists' opinions defend the idea that an appropriate bisphosphonate therapy can prevent this bone loss. [31][32][33][34] Clear identification of risk factors for osteoporosis in individual patients should aid treatment decisions about whether to use bisphosphonates and when to start them.…”
Section: Discussionmentioning
confidence: 99%
“…Some non-systematic reviews and specialists' opinions defend the idea that an appropriate bisphosphonate therapy can prevent this bone loss. [31][32][33][34] Clear identification of risk factors for osteoporosis in individual patients should aid treatment decisions about whether to use bisphosphonates and when to start them.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors related to ONJ have been characterized and include pre-existing dental pathology, the use of dental prostheses, or maxillofacial surgery. These should be avoided whenever bone-preserving therapy is administered, and patients should further benefit from regular dental checkups during therapy [33][34][35].…”
Section: Intravenous Bisphosphonatesmentioning
confidence: 99%
“…In summary, androgen-deprivation therapy (ADT) in prostate cancer patients leads to a clinically significant bone loss that translates into a higher fracture risk at 5 years of 19.4%, compared with 12.6% in nonusers (p Ͻ .001) [50,51]. Placebo-controlled trials have shown that pamidronate (60 mg i.v.…”
Section: Emerging Evidence On the Future Role Of Bisphosphonates In Cmentioning
confidence: 99%